GENETIC DIVERSITY ANALYSIS OF Camelina sativa LINES USING IPBS MARKERS: INSIGHTS INTO DIVERSITY, PRIMERS EFFICACY, AND CLUSTER ANALYSIS - Zinab Salehi; Danial Kahrizi; Leila Zarei; Hülya Dogan (Journal of Animal and Plant Sciences, 2025)
Camelina (Camelina sativa L.) is an oilseed plant valued for its low water and fertilizer needs, environmental adaptability, and rich fatty acid contents. In this study, genetic diversity among 16 camelina doubled haploid lines and the Soheil and Sepehr varieties was assessed using 15 inter-primer binding site (IPBS) retrotransposon primers to investigate their molecular characteristics. Fresh leaf samples were collected for DNA extraction using Dellaporta's method, followed by quantification and quality assessment using a NanoDrop and agarose gel electrophoresis. Polymerase chain reaction (PCR) was performed with IPBS retrotransposon primers. Amplified DNA fragments were separated via electrophoresis on an agarose gel and visualized under UV light. The study evaluated genetic variation among 18 doubled haploid lines of camelina using 15 IPBS retrotransposon primers, of which 14 produced scorable bands ranging from 200 to 5000 bp. A total of 325 bands were generated, with 83 showing polymorphism, resulting in an average polymorphism percentage of 25.41%. Primers IPBS (2076) and IPBS (2237) were the most effective, each yielding 10 polymorphic bands and high polymorphic information content (PIC) values of 0.30. The Jaccard genetic similarity matrix indicated moderate genetic diversity among the lines, with similarity values ranging from 0.4 to 0.9. Cluster analysis categorized the lines into four distinct groups, while principal coordinates analysis revealed that the first two components explained 78.99% of the total variation, corroborating the clustering results. Overall, the findings highlight the utility of IPBS markers in assessing genetic diversity in camelina lines, demonstrating their potential for future breeding programs. The scatter diagram generated from the principal coordinate analysis depicted the lines grouped into five clusters, showing some consistency with the cluster analysis results. The IPBS marker seems to be a suitable tool for assessing genetic diversity in camelina. The observed genetic diversity provides valuable insights for camelina breeding programs focused on developing cultivars with desirable traits.
Keywords: Camelina; doubled haploid; IPBS marker; molecular characteristic; PCR